Profissionalização docente e subordinação do trabalho educativo à lógica flexível da produção capitalista - Carvalho, Saulo Rodrigues [UNESP] (2016)
This work deals with the concept of Teacher Professional Identity, from the standpoint of historical materialism-Dialectical. The discussion of teacher professional identity is highlighted specifically during the capitalist restructuring of the production and standardization of flexible accumulation pattern. The same is presented as a prerogative for the training of teachers in a critical and autonomous perspective within the teaching professionalism, in order to overcome the identity crisis of the teacher's work. Similarly, the determinations of productive restructuring on the magisterium can influence the in the form of impoverishment of school subjects and replacing a based education in objective scientific knowledge by training in structural affinity with the changing demands of contemporary capitalism. In this sense, we put in question the concept of Teacher Professional Identity, questioning his prerogative as a way of overcoming the crisis brought by the changes of capitalism. Understanding it as a way to adapt the demands imposed by this productive dynamic, discuss their theoretical bases, putting on suspicion the concept of identity. Lastly we discuss the failure of the identity of the teacher limited to his professional particularity and the historical necessity of the apprehension of universality of educational work for teacher training.